Thermal Analysis of Transformer in Distribution - Safaat, Iqbal; Zulkifli, Mardzulliana; Sahari, Norain (Progress in Engineering Application and Technology, 2022)
In engineering, transformers are used in a wide variety of applications, some of which include the production, transmission, and distribution of energy. It does this by using the principle of electromagnetic induction, which converts an alternating current (A/C) with a specific voltage into a direct current (DC) with a different magnitude. In this research, will use 3D modelling to forecast the thermal performance of transformers. To conduct the simulation and get the thermal performance of the transformer, finite element analysis (FEA) method will be use. The simulation results will be compared to the actual results of the experiment, which will be conducted. The experimental thermal camera specifications will be compared with those of the other thermal cameras to determine which of the thermal cameras is the most effective one to utilize when assessing thermal performance.